Forming an Anti-Corruption Culture of Law Enforcement Agencies: National and International Experience - SITNIKOV, Pavel Vladimirovich; IBRAYEVA, Alua Salamatovna; ALDABERGENOV, Azamat Tynyshtykbayevich; BAIKENZHEYEV, Akhylbek S.; IBRAYEV, Nurlan Salamatovich (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
This article is concerned with the specific formation of an anti-corruption culture in the law enforcement system of the Republic of Kazakhstan. To this date, the country has formed a large base of legal acts regulating the fight against corruption but their effectiveness raises questions. In this context, it is necessary to use preventive measures both in society as a whole and in the field of public administration, including law enforcement agencies. One such measure is the formation of an anti-corruption culture. This study aims at analyzing global directions and approaches to the formation of an anti-corruption culture among law enforcement employees. The authors of the article consider the world experience of an anti-corruption struggle and the most efficient models of forming an anti-corruption culture in the sphere of law enforcement. The authors have proved that the anti-corruption culture of law enforcement agencies differs from that of other society members and revealed its specific features. The necessary condition for their effective neutralization is not only legal education but also the promotion of moral and ethical standards. According to the authors, this goal can be achieved through anti-corruption education that fosters a culture of involvement and consciousness, a clear rejection of corruption and the popularization of anti-corruption standards. In the course of the study, they highlight the main components of an anti-corruption culture among law enforcement employees and conclude on the further efforts scholars and lawmakers should make to develop a common worldview, scientific and legal concept of the fight against corruption.